Cooling asphalt pavement by increasing thermal conductivity of steel fiber asphalt mixture. (15th March 2021) - Yinfei, Du; Jiacheng, Wang; Jiaqi, Chen
Highlights: Steel fiber was used to prepare high-thermal-conductivity asphalt mixture. Steel fiber could increase the air voids content of asphalt mixture. Greater compaction work could induce a lower air voids content of asphalt mixture. Using steel fiber asphalt mixture could reduce the temperature of asphalt pavement. Abstract: High-temperature asphalt pavements will intensify urban heat island effect and cause many pavement distresses. In order to cool asphalt pavement, two types of steel fiber, curved hook steel fiber (CH-SF) and long sawtooth steel fiber (LS-SF), were used to increase the thermal conductivity of asphalt mixture. The results show that the addition of steel fiber increased the air voids content of asphalt mixture, of which CH-SF had a stronger influence. Six compaction levels were used to investigate the compaction characteristic of steel fiber asphalt mixture. It is found that greater compaction work would induce the mixtures to be further compacted. When the steel fiber asphalt mixtures were compacted to have an air voids content of about 4.0%, CH-SF was more effective to increase the thermal conductivity and splitting strength of asphalt mixture than LS-SF. The indoor irradiation test shows that using 1.0% CH-SF asphalt mixture below the top asphalt layer could reduce the temperature at the depth of 4 cm by 1.8 ℃. The findings in this study indicate that using CH-SF can increase the thermal conductivity of asphalt mixture, on the condition that the CH-SF asphalt mixture is compacted to have an appropriate air voids content.